Integrated membrane bioreactors modelling: A review on new comprehensive modelling framework. (June 2021) - Mannina, Giorgio; Alliet, Marion; Brepols, Christoph; Comas, Joaquim; Harmand, Jerome; Heran, Marc; Kalboussi, Nesrine; Makinia, Jacek; Robles, Ángel; Rebouças, Taise Ferreira; Ni, Bing-Jie; Rodriguez-Roda, Ignasi; et al.
Graphical abstract: Highlights: A literature review on integrated MBR modelling and control is presented. The use of integrated MBR models should be more encouraged. A new framework was proposed to pursue good practice for MBR modelling. Integrated MBR modelling applications to real case studies is needed. Abstract: Integrated Membrane Bioreactor (MBR) models, combination of biological and physical models, have been representing powerful tools for the accomplishment of high environmental sustainability. This paper, produced by the International Water Association (IWA) Task Group on Membrane Modelling and Control, reviews the state-of-the-art, identifying gaps for future researches, and proposes a new integrated MBR modelling framework. In particular, the framework aims to guide researchers and managers in pursuing good performances of MBRs in terms of effluent quality, operating costs (such as membrane fouling, energy consumption due to aeration) and mitigation of greenhouse gas emissions.